(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2023)
The main objective of this article is to understand how the identity aesthetics of scenic lighting designer Marcelo Flecha (Pequena Companhia de Teatro - São Luís-MA), with emphasis on the conception, construction and execution of shows “Pai e Filho” (2010) and “Ensaios Sobre a Memória ” (2019), observing in the lighting of these two shows what makes Flecha’s work so singular. This text focuses on the formative aspects of the illuminator, seeking to understand how the artist’s baggage is effective in his aesthetics.